2004
DOI: 10.1182/blood-2002-11-3568
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 and tumor necrosis factor alpha region haplotypes predict transplant-related mortality after unrelated donor stem cell transplantation

Abstract: Certain cytokine gene polymorphisms have been shown to correlate with outcome of human leukocyte antigen (HLA) identical sibling donor stem cell transplantation (SCT), but in unrelated donor SCT such information is scarce. We have studied the association between cytokine gene polymorphism and transplant-related mortality (TRM) in 182 unrelated SCTs performed at a single center. We found association of polymorphism in the tumor necrosis factor alpha (TNF␣) and interleukin-10 (IL-10) gene and TRM. Both the TNFd4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 23 publications
3
51
0
1
Order By: Relevance
“…7 In a large cohort of HLA-matched sibling transplants, the presence of the IL-10 ATA/ACC genotype in the recipient has been associated with a moderate risk of GVHD and lower risk of death in remission, 16 more severe GVHD occurring in groups without the IL-10 ATA haplotype. The study by Lin et al 16 assessed overall survival, allele frequency and genotypes at each IL-10 SNP and showed that the risk of death was the lowest in recipients who were homozygous for the -592A allele.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In a large cohort of HLA-matched sibling transplants, the presence of the IL-10 ATA/ACC genotype in the recipient has been associated with a moderate risk of GVHD and lower risk of death in remission, 16 more severe GVHD occurring in groups without the IL-10 ATA haplotype. The study by Lin et al 16 assessed overall survival, allele frequency and genotypes at each IL-10 SNP and showed that the risk of death was the lowest in recipients who were homozygous for the -592A allele.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of unrelated donor transplants, TRM was associated with the higher IL-10 producer GCC haplotype when present in the donor. 7 However, the lower producer allele (IL-10-1082A) has also been associated with poor survival. 22 Furthermore, it was shown that patients with ATA haplotypes required more prolonged immunosuppression due to increased incidence of cGVHD and were more susceptible to pulmonary aspergillosis, whereas the ACC haplotype reduced the risk of pulmonary aspergillosis ninefold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, the IL-10 promoter gene SNP was found to be associated with acute 10 or chronic GVHD, 11,12 or transplant-related mortality (TRM) in an allogeneic transplant setting. 13 Moreover, the role of IL-10 in the local host defense mechanism in the lungs may also affect the pathogenesis of IPA. 14 However, data on the association of the IL-10 promoter gene SNP with the pathogenesis of IPA after allogeneic SCT is scarce.…”
Section: ; Invasive Pulmonary Aspergillosis; Allogeneic Stem Cell Tmentioning
confidence: 99%
“…5 The role of some of these non-HLA genes have been studied (reviewed [6][7][8][9][10] ): single nucleotide polymorphisms and/or microsatellites within cytokine (-receptor) genes and other non-HLA encoded genes, including those of the innate immune system, may indeed influence HSCT outcome. [11][12][13][14][15][16][17] Genes in the TNF block, MICA/MICB and microsatellite markers are of specific interest because they are in linkage disequilibrium (LD) with the classical HLA genes and could be inherited together as one genetic unit. [13][14][15][18][19][20][21] The presence of FH in patients also affects the probability and speed of identifying a matched UD.…”
Section: Introductionmentioning
confidence: 99%